2019
DOI: 10.1039/c9tc00311h
|View full text |Cite
|
Sign up to set email alerts
|

Sol–gel magnetite inks for inkjet printing

Abstract: The article describes an easy-to-implement and print-ready composition for inkjet printing of magnetic structures, which can be used for security printing, coding, and marking, magnetic device fabrication or creation of micro-antennas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…Ferria hydrosol: Ferria hydrosol was prepared by the procedure described earlier [ 5 , 53 ]. Briefly, 2.5 g of iron (II) chloride tetrahydrate and 5 g of iron (III) chloride hexahydrate were dissolved in 100 mL of deionized water and 11 mL of ammonia was added rapidly under constant stirring.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ferria hydrosol: Ferria hydrosol was prepared by the procedure described earlier [ 5 , 53 ]. Briefly, 2.5 g of iron (II) chloride tetrahydrate and 5 g of iron (III) chloride hexahydrate were dissolved in 100 mL of deionized water and 11 mL of ammonia was added rapidly under constant stirring.…”
Section: Methodsmentioning
confidence: 99%
“…Enzymatic nanocomposites and hybrid materials are emerging classes of bioactive materials which attract a vast amount of attention due to the potential contained in such systems for a variety of applications. Enzymatic composites are intensively studied for the purposes of industrial applications, analytics, smart materials, and next-level nanotherapeutics [ 1 , 2 , 3 , 4 , 5 ]. Such composites may be synthesized in a variety of ways depending on the proposed application scenario, but among them, special attention is paid to sol-gel composites.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier it was demonstrated that rheologic parameters of the magnetite hydrosol could be optimized by mixing with diethylene glycol [28]. Figure 5A represents the main rheological parameters of the ink.…”
Section: Inkjet Printing Of Bacteria Sensorsmentioning
confidence: 99%
“…To pattern MNPs by inkjet printing, the inks with proper rheological parameters were prepared in the manner described earlier [28]. For that purpose, MNPs hydrosol was mixed with diethylene glycol in a ratio of 1:1 to increase its viscosity and decrease the surface tension of the ink to form a steady drop.…”
Section: Inkjet Printing Of Mnpsmentioning
confidence: 99%
“…In this regard, inkjet printing is a promising method for fast manufacturing large-scale high-resolution photonic coatings in an inexpensive way [ 18 , 19 , 20 , 21 ]. It is a noncontact deposition technology and avoids impurities or substrate breakdowns.…”
Section: Introductionmentioning
confidence: 99%